2023
DOI: 10.1007/s00330-023-09816-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of MRI in the prenatal diagnosis and classification of fetal microtia

Abstract: Objective To investigate the role of MRI in the diagnosis and classification of fetal microtia. Methods Ninety-five fetuses with suspected microtia based on ultrasound and MRI performed within 1 week were enrolled in this study. The diagnosis based on MRI was compared with postnatal diagnosis. Among the microtia cases suspected on the basis of MRI, mild and severe cases were further classified. In addition, external auditory canal (EAC) atresia was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Zemet (2020), Gai (2022), Arangio (2013) and co-authors, confirmed the added diagnostic value of fetal MRI for evaluation of fetal craniofacial anomalies in retrospective studies comparing MRI and US [10][11][12]. Other studies have focussed on the MRI imaging of specific features, pathology and measurements within the craniofacial anatomy, for example; the orbits [13][14][15]; orofacial clefts, including cleft lip and palate [16][17][18][19][20][21]; inner, middle and external ear structures [22][23][24][25]; the upper and lower jaw [26][27][28]; and skull shape deformities to include craniosynostosis [29][30][31]. Due to the relative rarity of craniofacial malformations, most fetal MRI studies are retrospective in nature, consist of case series studies, and there are a lack of control subjects to assess diagnostic accuracy in a clinical setting.…”
Section: Mri Of Fetal Craniofacial Featuresmentioning
confidence: 85%
“…Zemet (2020), Gai (2022), Arangio (2013) and co-authors, confirmed the added diagnostic value of fetal MRI for evaluation of fetal craniofacial anomalies in retrospective studies comparing MRI and US [10][11][12]. Other studies have focussed on the MRI imaging of specific features, pathology and measurements within the craniofacial anatomy, for example; the orbits [13][14][15]; orofacial clefts, including cleft lip and palate [16][17][18][19][20][21]; inner, middle and external ear structures [22][23][24][25]; the upper and lower jaw [26][27][28]; and skull shape deformities to include craniosynostosis [29][30][31]. Due to the relative rarity of craniofacial malformations, most fetal MRI studies are retrospective in nature, consist of case series studies, and there are a lack of control subjects to assess diagnostic accuracy in a clinical setting.…”
Section: Mri Of Fetal Craniofacial Featuresmentioning
confidence: 85%
“…Zemet (2020), Gai (2022), Arangio (2013) and co-authors, confirmed the added diagnostic value of fetal MRI for evaluation of fetal craniofacial anomalies in retrospective studies comparing MRI and US [1012]. Other studies have focussed on the MRI imaging of specific features, pathology and measurements within the craniofacial anatomy, for example; the orbits [1315]; orofacial clefts, including cleft lip and palate [1621]; inner, middle and external ear structures[2225]; the upper and lower jaw [2628]; and skull shape deformities to include craniosynostosis [2931]. Due to the relative rarity of craniofacial malformations, most MRI studies are retrospective in nature, consist of case series and case studies, and there is a lack of control subjects to assess diagnostic accuracy in a clinical setting.…”
Section: Introductionmentioning
confidence: 98%